The Marriage of Hydrazone‐Linked Covalent Organic Frameworks and MXene Enables Efficient Electrocatalytic Hydrogen Evolution - Chenyu Ma; Haiyan He; Jinlong Qin; Lang Luo; Yue Lan; Jian Zhang; Lu Yang; Quanguo Jiang; Huajie Huang (Small Structures, 2024)
Electrochemical water splitting is long regarded as a green and feasible pathway to realize the scalable hydrogen production, while the overall hydrogen evolution reaction (HER) efficiency is largely dependent on the electrocatalytic ability of the cathode catalysts. Herein, the in situ growth of hydrazone‐linked covalent organic framework (COF‐42) nanocrystals with a unique nanoflower‐shaped morphology on 2D ultrathin Ti3C2Tx MXene nanosheets (COF/Ti3C2Tx) is achieved through a convenient and robust stereoassembly strategy. Strikingly, the marriage of COF‐42 and Ti3C2Tx nanosheets not only offers multiscale porous channels for the fast transportation of electrolyte and electrons, but also enables the full exposure and activation of numerous catalytically active centers. As a consequence, the optimized COF/Ti3C2Tx nanoarchitecture displays exceptional HER properties in terms of a very low onset potential of 19 mV, a small Tafel slope of 50 mV dec−1 as well as reliable long‐term durability, which are comparable to those of commercial Pt/C catalyst. Density functional theory calculations further disclose that the rational combination of COF‐42 with Ti3C2Tx provides more diversified active positions with appropriate ΔGH values, thus leading to a boosted hydrogen generation rate.